Menstrual disorders following COVID-19 vaccination: a review using a systematic search - Smaardijk, Veerle R.; Jajou, Rana; Kant, Agnes; van Hunsel, Florence P. A. M. (Frontiers in Drug Safety and Regulation, 2024)
Menstrual disorders are commonly reported after COVID-19 vaccination and heavy menstrual bleeding was added to the product information of the COVID-19 vaccines of Moderna and Pfizer. The aim of this review,using a systematic search, is to provide an overview of available literature on the risk of menstrual disorders after COVID-19 vaccination. The review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. A PubMed search was performed on August 15, 2023, including solely quantitative studies in English and Dutch. A total of 61 studies were included, of which 40 were cross-sectional studies, 18 cohort studies, and three self-controlled case series. Outcomes included a wide variety of menstrual disorders, including changes in cycle length (n=54), changes in the amount of bleeding (n=44), changes in menses length (n=30), changes in the experience of (pre)menstrual pain (n=21), and breakthrough bleeding (n=18). All included studies found a higher percentage of at least one menstrual disorder in the first cycle after different types of COVID-19 vaccination and after different doses. In conclusion, evidence suggests that COVID-19 vaccines may cause menstrual changes in women of reproductive age. However, there is a need for more longitudinal studies because of important limitations in the study designs of many of the included studies. Although menstrual changes are short-lived and predominantly mild, it is important for women and health care professionals to be informed about these potential adverse reactions and to assess these events in clinical trials on vaccines.